2022
DOI: 10.1371/journal.pgph.0000655
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices of health care waste management among Zambian health care workers

Abstract: Poor management of health care waste poses a serious threat to the health of health care workers, patients and communities. In developing countries, adequate health care waste management (HCWM) is often a challenge. To address this, the Zambian Health Services Improvement Project with HCWM as a component, was implemented in five Zambian provinces (Luapula, Muchinga, Northern, North-Western and Western Provinces), under which this cross-sectional study was conducted to identify the knowledge, attitudes, and pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…11 The management of healthcare waste generation, treatment, storage, and disposal involves administrative agencies, managers, contractors in healthcare waste handling firms, and other stakeholders close to healthcare institutions. [12][13][14] The national health policy of Tanzania, for instance, has shown that sanitation difficulties have persisted as a public problem of concern that needs to be addressed appropriately despite innovative initiatives against environmental pollution and deforestation. 15 Managers, contractors, or bosses must carry out tasks like hiring sanitary health staff, buying equipment for handling healthcare waste, fostering a healthy and welcoming work environment, acquiring personal protective equipment, and guaranteeing and processing payments to their employers in order for healthcare waste handling to be effective.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…11 The management of healthcare waste generation, treatment, storage, and disposal involves administrative agencies, managers, contractors in healthcare waste handling firms, and other stakeholders close to healthcare institutions. [12][13][14] The national health policy of Tanzania, for instance, has shown that sanitation difficulties have persisted as a public problem of concern that needs to be addressed appropriately despite innovative initiatives against environmental pollution and deforestation. 15 Managers, contractors, or bosses must carry out tasks like hiring sanitary health staff, buying equipment for handling healthcare waste, fostering a healthy and welcoming work environment, acquiring personal protective equipment, and guaranteeing and processing payments to their employers in order for healthcare waste handling to be effective.…”
Section: Introductionmentioning
confidence: 99%
“…25 Sanitary personnel gather and move medical waste from the source to disposal locations or incinerators using tools including wheelbarrows, wheel buckets, crates, and/or plastic bags. 14 Depending on the pace of healthcare waste generation and timetable, the processes may be performed daily or weekly. 26 Sanitary employees have gotten close to problems including the gathering, transportation, storage, treatment, and disposal of solid waste from sources including healthcare facilities despite being removed from the generation of healthcare waste.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations